Personal Voice Assistant: from Inception to Everyday Application - Shazhaev, Ilman; Mikhaylov, Dmitry; Shafeeg, Abdulla; Tularov, Arbi; Shazhaev, Islam (Indonesian Journal of Data and Science, 2023)
The creation of automatic speech recognition systems is a popular trend in the development of information technology. These technologies are developing at a very fast pace, gradually covering more and more areas: already now we can say how firmly they have settled in our lives. The term "speech technologies" means a fairly large layer of information technologies, but one of the most advanced products in this area is a voice assistant, which includes the use of all types of speech technologies: speech recognition, speech synthesis, a system for developing and analyzing voice information, and voice biometrics. A voice assistant is software that allows you to control your device using voice commands. The range of possibilities does not end with the execution of commands; a modern assistant is even able to maintain a conversation with the user. Since the voice assistant is a complex innovation that consists of many different technologies, the task of a smart assistant is to ensure that they work smoothly with each other. Now there are many voice assistants on the market that can make life easier for a person. Now you don’t have to manually enter a question into a search engine or search for a song, you just need to say what you want, and the voice assistant will find everything on its own. But every year there are more and more assistants and it becomes more and more difficult for the average user to choose, because each assistant has its own characteristics. Nevertheless, the daily use of this technology is becoming more widespread. Another area that is rapidly developing is gaming. Using more and more innovations, the next logical step is to implement a voice assistant, at least at the training stage. However, real progress is out of the question for the time being.